2018
DOI: 10.1186/s12871-018-0657-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient-controlled analgesia with hydromorphone or sufentanil on postoperative pulmonary complications in patients undergoing thoracic surgery: a quasi-experimental study

Abstract: ObjectiveTo compare the analgesic effects of patient-controlled intravenous analgesia (PCA) with hydromorphone and sufentanil after thoracic surgery on postoperative pulmonary complications (PPCs).MethodsA total of 142 patients who were scheduled for thoracic surgery were randomly allocated to receive PCA with hydromorphone (group A: experimental group): hydromorphone 0.2 mg/kg + dezocine 0.5 mg/kg + ramosetron 0.6 mg diluted with normal saline to 200 mL; or with sufentanil (group B: control group): sufentanil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
2
18
0
1
Order By: Relevance
“…In addition to exerting analgesic effects, it has been shown that pretreatment with hydromorphone significantly reduces the levels of ROS in mouse glial cells under ischemic conditions and that the μ , δ , κ opioid receptors participate in the antioxidative effects of hydromorphone on glial cells [ 20 ]. Additionally, when used in postoperative pain management, hydromorphone had better anti-inflammatory effects than other sufentanil in patients who received thoracic surgery, as shown by lower levels of C-reactive protein (CRP) in the plasma and fewer pulmonary complications [ 42 ]. To investigate the role of hydromorphone in clinical patients receiving gynecological laparoscopic surgery, we used a dosage of hydromorphone equianalgesic to the dosage of morphine used in other studies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exerting analgesic effects, it has been shown that pretreatment with hydromorphone significantly reduces the levels of ROS in mouse glial cells under ischemic conditions and that the μ , δ , κ opioid receptors participate in the antioxidative effects of hydromorphone on glial cells [ 20 ]. Additionally, when used in postoperative pain management, hydromorphone had better anti-inflammatory effects than other sufentanil in patients who received thoracic surgery, as shown by lower levels of C-reactive protein (CRP) in the plasma and fewer pulmonary complications [ 42 ]. To investigate the role of hydromorphone in clinical patients receiving gynecological laparoscopic surgery, we used a dosage of hydromorphone equianalgesic to the dosage of morphine used in other studies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dezocine is a partial μ opioid receptor agonist [27,36,37]that is theoretically approximately equipotent with morphine. Clinical studies have also proved it has the same analgesic effect as morphine [38][39][40]. Dezocine is becoming one of the most popular postoperative analgesics in China and is often used in combination with opioids, such as sufentanil [15,27].…”
Section: Plos Onementioning
confidence: 99%
“…On combining fentanyl, which has a rapid onset time and short duration of action, with oxycodone or hydromorphone-opioids with a slower onset time but a longer duration of action-we can provide analgesia with a rapid onset time and long duration of action. In addition, to reduce the possibility of respiratory depression owing to the use of 2 opioids, we used a lower hourly dose than that commonly used during PCA (hourly dose of opioids in PCA in our hospital and this study: fentanyl, 0.008 mg/h; hydromorphone, 0.04 mg/h; and oxycodone, 0.2 mg/h vs commonly used opioid doses per hour during PCA: fentanyl, 0.015-0.060 mg/h (29)(30)(31); hydromorphone, 0.24-0.26 mg/h (32,33); and oxycodone, 0.3-1.2 mg/h (34)).…”
Section: Discussionmentioning
confidence: 66%